Pelatihan Mempergunakan Aplikasi Si Apik Berbasis Android Pada UMKM Kuliner Bakso Malang - grace gata; Siswanto; Yani Prabowo; Yuliazmi (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2020)
UMKM Malang Bakso Culinary Culinary have so far been aware of recording low financial transactions, recording financial transactions is considered difficult, small or simple business scale and mixed finance, causing UMKM to not know the financial condition of their business, Banks have difficulty analyzing the ability of UMKM, often inaccurate credit analysis, takes time and cost. Community service is carried out on micro small and medium businesses, namely poor meatball small businesses located in the Gang Masjid area, Petukangan Utara, South Jakarta. The activity carried out is training in recording financial information which is a difficult thing for small businesses to compile transactions made up to make financial reports that can be used as a reference to get credit from the government. In this case the SI APIK android-based application provides convenience in financial management by small and medium businesses. This activity is divided into 3 (three) stages of implementation, namely preparation, implementation and evaluation. The culmination of this community service is the training that held on November 23, 2019 at the Masjid Alley, Petukangan Utara, South Jakarta. In the UAT test, a questionnaire with a scale Likert scale of 5 was used. As a result, the respondents agreed (above 70.9%) that overall the training on recording financial information using the APIK android based application could help the owners and employees of UMKM Bakso Malang.